Type I interferons differentially modulate maternal host immunity to infection by Listeria monocytogenes and Salmonella enterica serovar Typhimurium during pregnancy - Agbayani, Gerard (Am J Reprod Immunol, 2018)
PROBLEM: IFN-alpha receptor deficiency (IFNAR(−/−)) enhances immunity to Listeria monocytogenes (LM) and Salmonella enterica serovar Typhimurium (ST) in the non-pregnant state by inhibiting pathogen-induced immune cell death. However, the roles of IFNAR signaling in modulating immunity to infection during pregnancy are not well-understood. METHOD OF STUDY: WT and IFNAR(−/−) mice were infected systemically with LM or ST. Bacterial burden in spleen and individual placentas was enumerated at day 3 post-infection. Immune cell numbers and percentages were quantified in spleen and individual placentas, respectively, through flow cytometry. Cytokine expression in serum, spleen and individual placentas was measured through cytometric bead array. RESULTS: IFNAR(−/−) mice exhibited decreased splenic monocyte numbers in non-pregnant and pregnant state, and an altered distribution of placental immune cell types in the non-infected state. IFNAR−/− mice controlled LM infection more effectively than wild-type even during pregnancy, and this correlated with enhanced serum IL-12 expression, despite reduced splenic monocyte numbers relative to WT controls. In contrast, pregnant IFNAR(−/−) mice unlike their non-pregnant counterparts exhibited increased susceptibility to ST infection which was associated with decreased serum IL-12 expression. CONCLUSION: Type I IFN responses differentially impact host resistance to LM and ST infection during pregnancy through modulation of immune cell distribution and cytokine responses.